HUMAN CAPITAL SEBAGAI STRATEGI PENGEMBANGAN SUMBER DAYA PROFESIONAL DI LEMBAGA ZAKAT NURUL HAYAT - Kusumaningtyas, Esa Ayu; Asegaf, M Maulana; Dikuraisyin, Basar (Program Studi Manajemen Zakat dan Wakaf, 2021)
The problem of human resources in zakat institutions has always been the most critical obstacle that hinders the effectiveness and accuracy of institutional development. Weaknesses, incompetence and dualism of professional work are often classic reasons that plague zakat institutions. This weakness needs to be formulated, given a solution and a way out to escape from the entanglement of the resource problem. Therefore, this study wants to offer an ideal conception of zakat human resources (amil) development through the locus treasury at the Nurul Hayat zakat institution in Surabaya. The research method used is qualitative with descriptive data analysis. Data was extracted through two methods; interviews and observations. Documentation is not used as it relates to resource performance. This study resulted in two significant findings: firstly, most of the amil in Nurul Hayat already have the ability in fiqh zakat, seen from the training followed and the work experience of each amil. Meanwhile, marketing ability is seen from the results of amil performance in achieving targets and implementing online marketing in the form of posting programs. For public speaking skills, it can be seen from the briefing conducted by amil Nurul Hayat to train communication and practice it. Second, the professionalism of amil in the management of zakat in Nurul Hayat has carried out his responsibilities by reporting the results that have been carried out and collected by the amil. In managing zakat funds, it is evident from the efforts to improve their abilities by participating in training and self-study by reading books. Persoalan sumber daya manusia pada lembaga zakat selalu menjadi kendala terpenting yang mengganjal efektifitas dan akurasi pengembangan lembaga. Kelemahan pada aspek kompetensi dan dualisme kerja profesional seringkali menjadi alasan klasik yang mendera lembaga zakat. Kelemahan inilah yang perlu dicari formulasinya, diberikan solusi dan jalan keluar untuk lepas dari jeratan problem sumber daya. Oleh karena itu, penelitian ini ingin memberikan tawaran konsepsi ideal pengembangan sumber daya manusia (amil) zakat melalui pembendaharaan locus di lembaga zakat Nurul Hayat Surabaya. Metode penelitian yang digunakan bersifat kualitatif dengan analisis data deskriptif. Data digali melalui dua metode; interview dan observasi. Dokumentasi tidak digunakan karena berkenaan dengan kinerja sumber daya. Hasil dari penelitian ini menghasilkan dua temuan penting, yaitu: pertamas sebagian besar amil di Nurul Hayat sudah memiliki kemampuan tentang fiqih zakat, dilihat dari pelatihan yang diikuti dan pengalaman pekerjaan dari setiap amil. Sedangkan, kemampuan pemasaran dilihat dari hasil kinerja amil berupa pencapaian target dan pelaksanaan pemasaran melalui online, berupa posting program-program. Untuk kemampuan public speaking, dapat dilihat dari briefing dilakukan oleh amil Nurul Hayat untuk melatih komunikasi dan mempraktikkannya. Kedua,, profesionalisme amil dalam pengelolaan zakat di Nurul Hayat, sudah melaksanakan tanggung jawabnya dengan melaksanakan pelaporan hasil yang telah dikerjakan dan dihimpun oleh amil. Dalam mengelola dana zakat, terbukti dari adanya upaya untuk meningkatkan kemampuannya dengan mengikuti training dan belajar mandiri dengan membaca buku.